PELATIHAN PENGOLAHAN DAN PENGEMASAN RUMPUT LAUT MENJADI SELAI DI DESA LEMBONGAN KECAMATAN NUSA PENIDA KABUPATEN KLUNGUNG - Wiadnyani, A.A.I.S; Widarta, I.W.R.; Puspawati, N.N.; Indri H, N.M.; Kartika, I.D.P. (Buletin Udayana Mengabdi, 2018)
Nusa Lembongan is a small island near Nusa Ceningan Island about 2 km south west of Nusa Penida. Nusa Lembongan island has 4 km length and 1-1.5 km wide; is about 11 km southeast of Bali. The small island is a district in Klungkung regency. Most population worked as seaweed farmer and in tourism sector. Seaweed is main commodity in Nusa Lembongan. People in Lembongan village only sold seaweed in fresh form or dry form without further processing. They did not know use of seaweed as jam. Problem solution method used in this research was introduction and training of processing seaweed to jam and its packaging and labeling. Counseling, training and assistance activities for processing seaweed to jam run well in which KWT Segara Caksu can produce the processed product well. Packaging and labeling of the product may be also done well and resulting in product with interesting identity and appearance.